Pricing the Sun : a hedonic approach on the influence of photovoltaic systems on house prices in Sweden - Bolin, Axel (SLU/Dept. of Economics, 2019)
There is a growing concern regarding climate change and its potential damage on both ecosystems and human welfare. An increased production of renewable energy would enable a more sustainable lifestyle. Households that install solar panels to produce electricity from solar radiation are subsidized by the Swedish government to increase the production of renewable energy. However, it is still a relatively costly investment and households may therefore be hesitant to invest in solar panels. Knowledge on the expected influence on house prices by solar panels would enable households to make better informed decisions on whether to invest in solar panels or not. To investigate this hedonic regression is conducted using panel data on house sales in Sweden from 2012 to the end of 2018. The results strongly suggest that solar panels increase house prices, which makes it reasonable for households to expect an increased house price from the investment.